2018
DOI: 10.1093/cvr/cvy222
|View full text |Cite
|
Sign up to set email alerts
|

Nitroglycerine limits infarct size through S-nitrosation of cyclophilin D: a novel mechanism for an old drug

Abstract: Low dose NTG given prior to reperfusion reduces myocardial infarct size by preserving eNOS function, and the subsequent eNOS-dependent S-nitrosation of cyclophilin D, inhibiting cardiomyocyte necrosis. This novel pharmacological action of NTG warrants confirmation in clinical studies, although our data in human biopsies provide promising preliminary results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 50 publications
1
36
0
1
Order By: Relevance
“…On the other hand, the CyA analogs alisporivir/debio-025 [238], sanglifehrin A [234,312] and (NIM811) [240,313] are also showing progress against IRI in the myocardium, liver, and brain in animal models. Although not a CyA analog, it has been recently shown that the classic vasodilator nitroglycerine (glyceryl trinitrate) also inhibits CyD via S -nitrosation, and therefore limits I/R-driven myocardial infarction in rabbits [314].…”
Section: Therapeutics: the Pharmacological Approachmentioning
confidence: 99%
“…On the other hand, the CyA analogs alisporivir/debio-025 [238], sanglifehrin A [234,312] and (NIM811) [240,313] are also showing progress against IRI in the myocardium, liver, and brain in animal models. Although not a CyA analog, it has been recently shown that the classic vasodilator nitroglycerine (glyceryl trinitrate) also inhibits CyD via S -nitrosation, and therefore limits I/R-driven myocardial infarction in rabbits [314].…”
Section: Therapeutics: the Pharmacological Approachmentioning
confidence: 99%
“…Повышение сродства гемоглобина к кислороду (СГК) в крови и уменьшение потока кислорода в ткани при реперфузии под влиянием нитроглицерина и нитропруссида натрия способствовало снижению в печени уровня диеновых конъюгатов (ДК), малонового диальдегида и оснований Шиффа, указывая на уменьшение активности свободнорадикальных процессов перекисного окисления липидов (ПОЛ). Одновременно в печени под влиянием доноров NO в конце реперфузии происходит нормализация уровня α-токоферола, ретинола и активности каталазы Показано, что протективный эффект нитроглицерина наблюдается в условиях ишемии-реперфузии сердца [10]. Защитное действие доноров NO при ИРП можно обосновать улучшением условий микроциркуляции и снижением синтеза молекул межклеточной адгезии [11].…”
Section: влияние доноров No на развитие постишемических расстройств вunclassified
“…The general role of • NO for cardioprotection is also supported by numerous reports on loss of cardioprotective effects of • NO or • NO-related therapies upon treatment with the inhibitor of all NOS isoforms, N G -nitro-l-arginine methyl ester (l-NAME) (only citing a few [4,6,15,26]). Also exogenous administration of tetrahydrobiopterin (BH 4 ), an essential cofactor for eNOS function, improved ischemic damage in isolated hearts subjected to I/R [27,29].…”
mentioning
confidence: 91%
“…The cardioprotective properties of eNOS and • NO are widely accepted and were extensively reviewed in the past [9,24] and redefined in recent years [3]. The cardioprotection afforded by • NO (e.g., from nitrovasodilators such as nitroglycerin [13]) largely depends on the prevention of mitochondrial permeability transition pore (mPTP) opening via S-nitros(yl)ation of the mPTP regulator cyclophilin D during reperfusion [4]. This mechanism reflects a major detrimental process in ischemia/reperfusion (I/R) damage leading to excessive reactive oxygen species (ROS) formation/release as well as onset of apoptotic cell death [7,21].…”
mentioning
confidence: 99%
See 1 more Smart Citation